(untitled) (Ukrainian Journal of Ophthalmology, 2025)
Background: An 810-nm diode-laser transpupillary thermotherapy (TTT) is used as monotherapy in the treatment of small choroidal melanomas (CM; measuring ? 3-4 mm in prominence). We developed an advanced methodology for performing the TTT, which involves four sessions delivered daily over four consecutive days. Purpose: To examine ultrastructural features of therapeutic pathomorphosis after TTT delivered using the developed methodology in enucleated eyes with choroidal melanoma in which eye-preserving treatment was not feasible. Material and Methods: Material for electron microscopy was obtained from enucleated eyes of seven CM patients who had been treated with TTT delivered over one to four sessions. One patient had undergone one, two had undergone two, two had undergone three, and two had undergone four daily TTT sessions before enucleation, with an 810-nm diode laser (Iridis Quantel medical, France) in a continuous mode, and the power was gradually increased from the initial 200 mW to about 1800 mW until the desired endpoint was achieved. Biopsy fragments were fixed in 2.5% glutaraldehyde in phosphate buffer (pH 7.4), post-fixed with 1% osmium tetroxide in phosphate buffer (pH 7.4), dehydrated through an ascending ethanol series, and embedded in an Epon/Araldite mix. Thereafter, ultra-thin sections were cut, stained with lead citrate according to the procedure described by Reynolds, and observed with a PEM-100-01 Transmission Electron Microscope. Results: In our ultrastructural studies of choroidal melanoma after TTT delivered using the developed methodology, the most pronounced manifestations of therapeutic pathomorphosis were observed at day 4, and the developed methodology was substantiated by the ultrastructural findings. The therapeutic pathomorphosis in the melanoma tissue in response to 810-nm diode laser irradiation manifested itself as dry or wet necrosis, which was partial after the first treatment session, but a complete destruction of tumor cells at a depth of ? 4 mm from the irradiated surface was observed after four days of daily sessions. This indicates that our TTT delivery methodology can be used for treatment of small (T1) CM (measuring ? 3 mm in prominence and ? 12 mm in basal dimension). Conclusion: In our ultrastructural studies, the most pronounced changes in choroidal melanoma tissue manifested themselves as dry or wet necrosis, and were observed at day 4 of daily sessions of 810-nm diode laser TTT.